2010
DOI: 10.1080/03014223.2010.513396
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the number of nymphal instars inNysius huttoniWhite (Hemiptera: Lygaeidae)

Abstract: The number of nymphal instars of Nysius huttoni White was investigated at five constant temperatures (15, 20, 25, 30 and 3590.58C), one fluctuating (laboratory room conditions) temperature and three photoperiods (16-h, 12-h, and 8-h photophases) in the laboratory. Nymphs passed through four to six instars before they emerged as adults, individuals with five instars formed over 90% of the population, whereas those with four or six instars formed 4.2Á5.8 and 1.6Á2.9% respectively. Two nymphs were each recorded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…There may be differences in life history patterns between species or even geographically within a species. The usual number of nymphal instars is 5, as in other lygaeoid bugs, but Millikin (1918) reported 4 to 6 nymphal instars and this is supported by Wei (2010), who observed similar variation in the New Zealand species, N. huttoni White. Wei found the number of instars was positively correlated to rearing temperature.…”
Section: K Family Lygaeidae Subfamily Orsillinae -False Chinch Bugsmentioning
confidence: 90%
“…There may be differences in life history patterns between species or even geographically within a species. The usual number of nymphal instars is 5, as in other lygaeoid bugs, but Millikin (1918) reported 4 to 6 nymphal instars and this is supported by Wei (2010), who observed similar variation in the New Zealand species, N. huttoni White. Wei found the number of instars was positively correlated to rearing temperature.…”
Section: K Family Lygaeidae Subfamily Orsillinae -False Chinch Bugsmentioning
confidence: 90%
“…In the laboratory, variation in the number of instars is affected by both temperature and photoperiod, with lower numbers of instars more frequent at lower temperatures (Wei 2010). This suggests that flexibility in the number of larval instars may aid survival under changing environmental conditions (Wei 2010). N. huttoni normally have three generations per year in their natural range and overwinter as adults; therefore, a shorter nymphal stage could potentially be Phelan and Frumhoff (1991), Root and Chaplin (1976) Oncopeltus fasciatus Typical clutch size is approximately 30 eggs though this appears to be highly variable (recorded clutch sizes range from 5 to more than 50).…”
Section: Developmentmentioning
confidence: 99%
“…In this species, the number of larval instars ranges from three to seven, though individuals with five instars still form the majority. In the laboratory, variation in the number of instars is affected by both temperature and photoperiod, with lower numbers of instars more frequent at lower temperatures (Wei ). This suggests that flexibility in the number of larval instars may aid survival under changing environmental conditions (Wei ).…”
Section: Phylogenetic Status and Basic Biologymentioning
confidence: 99%
“…It has been shown that moulting is a period of high activity and regulation of several processes such as digestion, transport, proteolysis and cell death [6][7][8][9]. Likewise, larval moults can vary in number and frequency in response to environmental conditions such as temperature and diet [10,11]. Thus, the larval stage is highly responsive at many functional levels.…”
Section: Introductionmentioning
confidence: 99%